Secondary Sclerosing Cholangitis Following Coronavirus Disease 2019 (COVID-19): A Multicenter Retrospective Study. (29th July 2022) - Hunyady, Peter; Streller, Lea; Rüther, Darius F; Groba, Sara Reinartz; Bettinger, Dominik; Fitting, Daniel; Hamesch, Karim; Marquardt, Jens U; Mücke, Victoria T; Finkelmeier, Fabian; Sekandarzad, Asieb; Wengenmayer, Tobias; et al.
Abstract: Background: Secondary sclerosing cholangitis (SSC) is a rare disease with poor prognosis. Cases of SSC have been reported following coronavirus disease 2019 (COVID-SSC). The aim of this study was to compare COVID-SSC to SSC in critically ill patients (SSC-CIP) and to assess factors influencing transplant-free survival. Methods: In this retrospective, multicenter study involving 127 patients with SSC from 9 tertiary care centers in Germany, COVID-SSC was compared to SSC-CIP and logistic regression analyses were performed investigating factors impacting transplant-free survival. Results: Twenty-four patients had COVID-SSC, 77 patients SSC-CIP, and 26 patients other forms of SSC. COVID-SSC developed after a median of 91 days following COVID-19 diagnosis. All patients had received extensive intensive care treatment (median days of mechanical ventilation, 48). Patients with COVID-SSC and SSC-CIP were comparable in most of the clinical parameters and transplant-free survival was not different from other forms of SSC ( P = .443, log-rank test). In the overall cohort, the use of ursodeoxycholic acid (UDCA) (odds ratio [OR], 0.36 [95% confidence interval CI, .16–.80], P = .013; log-rank P < .001) and high serum albumin levels (OR, 0.40 [95% CI, .17–.96], P = .040) were independently associated with an increased transplant-free survival, while the presence of liver cirrhosis (OR, 2.52 [95% CI, 1.01–6.25], P = .047) was associated with worse outcome. Multidrug-resistant organism (MDRO) colonization or infection did not impact patients' survival. Conclusions: COVID-SSC and CIP-SSC share the same clinical phenotype, course of the disease, and risk factors for its development. UDCA may be a promising therapeutic option in SSC, though future prospective trials are needed to confirm our findings. Abstract : We compared secondary sclerosing cholangitis (SSC) following COVID-19, with SSC in critical ill patients in a multicenter study. Both SSC entities shared the same clinical phenotype, course of disease, and risk factors for its development.